Multi-institutional study of peritoneal sarcomatosis from uterine sarcoma treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Issue 11 (November 2017) - Sardi, Armando; Sipok, Arkadii; Baratti, Dario; Deraco, Marcello; Sugarbaker, Paul; Salti, George; Yonemura, Yutaka; Sammartino, Paolo; Glehen, Olivier; Bakrin, Naoual; Díaz-Montes, Teresa P.; Gushchin, Vadim
Abstract: Objective: Uterine sarcoma (US) is a rare tumor representing 1% of female genital tract malignancies. Peritoneal sarcomatosis (PS) after US, diminishes median overall survival (OS) and progression-free survival (PFS) with cytoreductive surgery (CRS) alone, with or without systemic chemotherapy is <1 year and 6 months, respectively. A multi-institutional review of PS from US was conducted to evaluate CRS and hyperthermic intraperitoneal chemotherapy (HIPEC) and effects on survival outcomes. Methods: A retrospective review of 36 patients from 7 specialized international centers was performed. Selection criteria included PS of uterine origin with CRS/HIPEC treatment. Clinical data were analyzed. OS and PFS were estimated with Kaplan-Meier method. Results: Thirty-six patients underwent a total 38 HIPEC procedures performed from 2005 to 2014; 35 previous treatment and 1 primary treatment. Twenty-nine (81%) LMS patients, 3 (8%) endometrial stromal sarcoma (ESS), 3 (8%) adeneosarcoma (AS), and 1 (3%) categorized as other. Median PCI was 16 (range: 2–39), 10 patients had PCI ≥20. Thirty-four patients (94%) had complete cytoreduction (CC 0–1), 19 patients recurred. CRS/HIPEC OS at 1, 3, and 5-years was 75%, 53%, and 32% respectively, with median OS of 37 months (CI 95%: 20–54). PFS in 32 patients with CC at 1, 3, and 5-years was 67%, 32% and 32%, respectively with median PFS of 18.9 months (CI 95%: 6.7–31). Conclusions: CRS/HIPEC is a promising treatment modality for patients with PS. Histological subtype may influence survival. A global prospective registry of patients to further assess the efficacy of CRS/HIPEC is needed.